Investigation of Various Tissue Culture Monolayers Sensitivity in Detection of Clostridium difficile Toxin - MH Salari; N Badami; N Sadeghifard; F Amin Harati (Tehran University of Medical Sciences, 2008)
Backround: Clostridium difficile is the most common cause of nosocomial diarrhea. It is usually a consequence of antibiotic treatment, but sporadic cases can occur. The purpose of this study was to investigate five tissue culture monolayers sensitivity in detection of C. difficile-toxin. Methods: A total of 402 stool samples from patients with nosocomial diarrhea hospitalized in three hospitals of Tehran University of Medical Sciences (TUMS) were collected. The samples were cultured on a selective cycloserine cefoxitin fructose agar (CCFA) and incubated in anaerobic conditions, at 37 °C for 4 days. Isolates were characterized to species level by conventional biochemical tests. Bacterial cytotoxicity was assayed on five tissue culture monolayers. Results: Our findings show that of the total patients, 24 toxigenic C. difficile (6%) were isolated. All 24 C. difficile toxins showed cytotoxic effect at ³ 1:10 dilution on Hela, Hep2, Vero, McCoy and Mdck cells after 16, 20, 24, 24 and 30 hours, respectively. C. difficile toxin showed cytotoxic effect at ³ 1:100 dilutions only on Hela cell monolayer after 48 hours. Conclusion: Hela cell monolayer may be a satisfactory substitute for the detection of C. difficile toxin in clinical specimens.